Kewirausahaan dari Abu Taqiyya ke Starbucks dan Kopi Nusantara - Jusmaliani (Jurnal Ekonomi dan Pembangunan, 2025)
This model aims to visualize the Islamic entrepreneurship concept through observation toward coffee industry which has strong both upward and backward lingkage. In Islamic paradigm, this method is called “istiqra” or that is familiar with the inductive approach. Coffee was choosen as it was originated from Arab where Islam firstly come from. This model was started by conducting “tafakur” and “tadabbur” (i.e. deep contemplation or thorough analysis of certain phenomena which is highly recommended in Islam). The important point from this model is that those benefits from entrepreneurship process are allocated to three activities: consumption, investment, and charity for community. The last allocation is closely related to the long term objective from a Muslim (i.e. heaven). Thus, this model is expected to be applied in other topics in the future.